Deletion of a Cyclic AMP Receptor Protein Homologue Diminishes Germination and Affects Morphological Development of Streptomyces coelicolor - Derouaux, A. (American Society for Microbiology, 2004)
Open reading frame SCO3571 of Streptomyces coelicolor encodes a protein of the cyclic AMP (cAMP) receptor protein (CRP) superfamily of regulatory proteins. A mutant revealed a dramatic defect in germination, followed by growth delay and earlier sporulation. This phenotype correlates with those of an adenylate cyclase (cya) mutant that cannot synthesize cAMP. This finding suggests that S. coelicolor may use a Cya-cAMP-CRP system to trigger complex physiological processes such as morphogenesis.